Efficacy, safety, Low density lipoprotein cholesterol lowering, and calculated 10-year cardiovascular risk reduction of alirocumab and evolocumab in addition to maximal tolerated cholesterol lowering therapy: a post-commercialization study. Issue 1 (December 2017) - Shah, Parth; Glueck, Charles; Goldenberg, Naila; Min, Sarah; Mahida, Chris; Schlam, Ilana; Rothschild, Matan; Huda, Ali; Wang, Ping
Abstract Background Efficacy and safety of proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors, alirocumab (ALI) and evolocumab (EVO) have previously been evaluated through controlled clinical trials with selective patient groups. Post-commercially, in patients with heterozygous familial hypercholesterolemia (HeFH) and/or cardiovascular disease (CVD) with suboptimal LDL cholesterol (LDLC) lowering on maximal tolerated cholesterol lowering therapy, we assessed efficacy and safety of ALI and EVO. Methods Post-commercially, we started 25 patients on ALI 75 mg, 15 on ALI 150 mg, and 32 on EVO 140 mg bi-weekly added to entry LDLC lowering regimen, with follow-up for a median 24 weeks. History, physical exam, demographics, and adverse event data were collected. Changes in LDLC and AHA and NIH calculated 10-year CVD risks were assessed on ALI and EVO. Results Of 72 patients, 25 had HeFH only, 25 CVD only, 22 had both, median age was 65 years, 63% females, 38% males, 86% Caucasian, 11% African-Americans, 17% diabetics, 63% on anti-hypertensives, and 7% smokers. At entry, 30 (42%) were on a statin and 42 (58%) could not tolerate any statins. At 24-weeks, median LDLC decreased on ALI 75 mg from 117 to 62 mg/dL (−54%), on ALI 150 mg from 175 to 57 mg/dL (−63%), and on EVO 140 mg from 165 to 69 mg/dL (−63%), p <0.0001 for all. Absolute and percent LDLC reduction did not differ (p >.05) between ALI 150 and EVO 140 mg, but were less on ALI 75 mg vs ALI 150 mg and EVO 140 mg (p <.05). Percent reductions in 10-year CVD risks by AHA and NIH calculators, respectively were ALI 75 mg −22 and −44%, ALI 150 mg −31 and −50%, and EVO 140 mg −29 and −56%, p ≤.002 for all. The three most common adverse events included flu-like myositis 10%, respiratory tract symptoms 8%, and injection site reaction 6%. Conclusion In patients with HeFH and/or CVD, LDLC was lowered by 63% on EVO and ALI 150 mg, and 54% on ALI 75 mg. Adverse events were minimal and tolerable. ALI and EVO represent paradigm shifts in LDLC lowering. Long term, post-commercial safety and efficacy remain to be determined.